Anode void space depletion for high content silicon carbon anodes for lithium ion batteries
By designing a porous carbonaceous coating and spherical recessed structure on the anode electrode of a lithium-ion battery, the problem of electrode coating rupture caused by the expansion of silicon particles in the lithiated state is solved, and the energy density and circulation capacity of the battery are improved.
Patent Information
- Application Number
- CN202311424309.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2023-10-30
- Publication Date
- 2024-12-31
AI Technical Summary
The expansion of the anode electrode of the lithium-ion battery in the lithiated state causes the electrode coating to rupture and failure, affecting the energy density and circulation capacity of the battery.
A porous carbonaceous anode electrode coating is designed. By forming spherical recesses on the electrode substrate and attaching silicon particles, the silicon particles are expanded into the recesses in a lithiated state, maintaining conductive contact, and doping them with nitrogen, phosphorus and silver. , tin or lithium alloying materials to anchor silicon particles.
It effectively increases the energy density of the anode electrode, avoids the rupture of the electrode coating, realizes stable expansion and conductivity of silicon particles, and improves the circulation capacity and stability of the battery.
Smart Images

Figure CN119230741A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an anode electrode including a porous electrode coating and a method for preparing the same, wherein the porous electrode coating enables expanded silicon particles to expand into pores. Background Art
[0002] Electrochemical energy storage devices, such as lithium-ion batteries, can be used to power a variety of items such as toys, consumer electronics, and motor vehicles. Typically, a battery includes two electrodes, as well as an electrolyte component and / or a separator. One of the two electrodes typically serves as the positive electrode, or cathode, while the other serves as the negative electrode, or anode. Electrochemical cells can be broadly divided into primary batteries and secondary batteries. Primary batteries, also called disposable batteries, are intended to be used until exhausted, after which they are simply replaced with new batteries. Secondary batteries, more commonly known as rechargeable batteries, employ a specific chemical composition that allows such batteries to be repeatedly recharged and reused.
[0003] Rechargeable batteries can be in solid form, liquid form, or a solid-liquid hybrid form. A separator and / or an electrolyte can be disposed between the negative electrode and the positive electrode. In a rechargeable lithium-ion battery, an electrolyte is typically used to conduct lithium ions between the electrodes. Typically, lithium-ion batteries work by reversibly transferring lithium ions back and forth between the negative electrode and the positive electrode. For example, lithium ions can move from the positive electrode to the negative electrode during charging of the battery and move in the opposite direction when the battery is discharged. The ability of the battery electrodes to repeatedly insert and extract lithium ions from their respective structures determines the actual long-term charge capacity of the battery cell.
[0004] Energy density describes how much energy a battery contains in proportion to the weight of the battery. A higher energy density reflects a higher capacity of the battery to deliver energy. Summary of the invention
[0005] An anode electrode for a lithium-ion battery cell is provided, the anode electrode comprising silicon and a porous carbonaceous anode electrode coating. The anode electrode comprises: an electrode substrate comprising a current collector; and a porous carbonaceous anode electrode coating. The electrode coating comprises: a surface material comprising graphite, wherein the surface material comprises a plurality of spherical depressions; carbon particles; and a plurality of silicon particles, the plurality of silicon particles being attached to inner walls of the plurality of spherical depressions. The spherical depressions are configured to receive expansion of the plurality of silicon particles when the silicon particles are in a lithiated state.
[0006] In some embodiments, each of the plurality of spherical depressions includes a portion of the plurality of silicon particles. When the plurality of silicon particles are in an unlithiated state, each of the plurality of spherical depressions includes an internal volume that is at least three times the volume of the silicon particles in the unlithiated state.
[0007] In some embodiments, each of the plurality of silicon particles is permanently bonded to an inner wall of the plurality of spherical depressions such that the plurality of silicon particles remain in conductive contact with the surface material through the lithiated state and the un-lithiated state.
[0008] In some embodiments, the porous carbonaceous anode electrode coating is doped with nitrogen, phosphorus, silver, tin, lithium alloying materials, or conductive atoms to anchor silicon to the surface material.
[0009] In some embodiments, when the plurality of silicon particles are in a lithiated state, the anode electrode expands in volume by at least 5% compared to a volume of the anode electrode when the plurality of silicon particles are in an un-lithiated state.
[0010] According to an alternative embodiment, a battery cell is provided, comprising an anode electrode for a lithium-ion battery cell, the anode electrode comprising silicon and a porous carbonaceous anode electrode coating. The battery cell comprises an anode electrode. The anode electrode comprises: an electrode substrate comprising a current collector; and a porous carbonaceous anode electrode coating. The electrode coating comprises a surface material having graphite. The surface material comprises a plurality of spherical depressions, carbon particles, and a plurality of silicon particles attached to the inner walls of the plurality of spherical depressions. The spherical depressions are configured to receive expansion of the plurality of silicon particles when the silicon particles are in a lithiated state. The battery cell also comprises a cathode electrode and an electrolyte.
[0011] In some embodiments, each of the plurality of spherical depressions includes a portion of the plurality of silicon particles. When the plurality of silicon particles are in an unlithiated state, each of the plurality of spherical depressions includes an internal volume that is at least three times the volume of the silicon particles in the unlithiated state.
[0012] In some embodiments, each of the plurality of silicon particles is permanently bonded to an inner wall of the plurality of spherical depressions such that the plurality of silicon particles remain in conductive contact with the surface material through a lithiated state and an un-lithiated state.
[0013] In some embodiments, the porous carbonaceous anode electrode coating is doped with nitrogen, phosphorus, silver, tin or other lithium alloying materials or conductive atoms to anchor silicon to the surface material.
[0014] According to an alternative embodiment, a method of manufacturing an anode electrode for a lithium-ion battery cell is provided, the anode electrode comprising silicon and a porous carbonaceous anode electrode coating. The method includes: attaching a plurality of silicon particles to each of a plurality of low-temperature burnout particles, the plurality of low-temperature burnout particles being configured to evaporate due to a burnout process. The method also includes: generating a mixture. The mixture includes: a plurality of low-temperature burnout particles, each of the low-temperature burnout particles including the plurality of silicon particles; a polymer material configured to generate conductive graphite due to a burnout process; and carbon particles. The method also includes: applying the mixture as a plurality of active material particles to an electrode substrate; and running a burnout process on the plurality of active material particles. The burnout process: converts the polymer material into the graphite to form a conductive surface material of the plurality of active material particles; and evaporates the plurality of low-temperature burnout particles, thereby leaving a plurality of spherical depressions in the surface material, one of the plurality of spherical depressions being used for each of the plurality of low-temperature burnout particles. The burnout process also causes the plurality of silicon particles to attach to the inner walls of the plurality of spherical depressions. The spherical depressions are configured to receive expansion of the plurality of silicon particles when the silicon particles are in a lithiated state.
[0015] In some embodiments, attaching the plurality of silicon particles to each of the plurality of low temperature burnout particles configured to evaporate as a result of the burnout process includes attaching the plurality of silicon particles to a plurality of polystyrene foam balls.
[0016] In some embodiments, the method further includes selecting a plurality of low temperature burnout particles configured for vaporization due to a burnout process in a size range configured such that a volume of the low temperature burnout particles configured for vaporization due to a burnout process is at least three times a volume of the silicon particles in an unlithiated state.
[0017] In some embodiments, attaching the plurality of silicon particles to each of the plurality of low temperature burnout particles configured for vaporization due to the burnout process includes rolling the plurality of low temperature burnout particles configured for vaporization due to the burnout process in silicon dust.
[0018] In some embodiments, applying the mixture to the electrode substrate includes applying the mixture as a slurry.
[0019] In some embodiments, applying the mixture to the electrode substrate includes applying the mixture by an electrodeposition process.
[0020] In some embodiments, applying the mixture to the electrode substrate includes utilizing a vacuum drum device on the electrode substrate to achieve a desired dispersion of the active material particles on the electrode substrate and to remove excess active material particles.
[0021] In some embodiments, the method further comprises: doping the mixture with nitrogen, phosphorus, silver, tin, or lithium alloying atoms, all for anchoring the silicon particles to the inner wall.
[0022] In some embodiments, the method further comprises: adding a binder, carbon black, or carbon nanotubes to the mixture.
[0023] The present invention also includes the following scheme:
[0024] Solution 1. An anode electrode for a lithium-ion battery cell, the anode electrode comprising silicon and a porous carbon anode electrode coating, the anode electrode comprising:
[0025] an electrode substrate including a current collector; and
[0026] A porous carbonaceous anode electrode coating comprising:
[0027] A surface material comprising graphite, wherein the surface material comprises a plurality of spherical depressions;
[0028] Carbon particles; and
[0029] A plurality of silicon particles are attached to inner walls of the plurality of spherical depressions, wherein the spherical depressions are configured to receive expansion of the plurality of silicon particles when the silicon particles are in a lithiated state.
[0030] Option 2. The anode electrode according to Option 1, wherein each of the plurality of spherical depressions includes a portion of the plurality of silicon particles; and
[0031] Wherein, when the plurality of silicon particles are in an unlithiated state, each of the plurality of spherical depressions includes an internal volume that is at least three times the volume of the silicon particle in the unlithiated state.
[0032] Option 3. An anode electrode according to Option 1, wherein each of the plurality of silicon particles is permanently bonded to an inner wall of the plurality of spherical depressions, so that the plurality of silicon particles remain in conductive contact with the surface material through the lithiated state and the un-lithiated state.
[0033] Option 4. An anode electrode according to Option 1, wherein the porous carbonaceous anode electrode coating is doped with nitrogen, phosphorus, silver, tin, lithium alloying materials or conductive atoms to anchor the silicon to the surface material.
[0034] Option 5. An anode electrode according to Option 1, wherein when the plurality of silicon particles are in the lithiated state, the anode electrode expands in volume in the range of 0% to 5% compared to the volume of the anode electrode when the plurality of silicon particles are in the unlithiated state.
[0035] Solution 6. A battery cell, comprising an anode electrode for a lithium-ion battery cell, the anode electrode comprising silicon and a porous carbonaceous anode electrode coating, the battery cell comprising:
[0036] The anode electrode comprises:
[0037] an electrode substrate including a current collector; and
[0038] The porous carbon anode electrode coating comprises:
[0039] A surface material comprising graphite, wherein the surface material comprises a plurality of spherical depressions;
[0040] Carbon particles; and
[0041] a plurality of silicon particles attached to inner walls of the plurality of spherical depressions, wherein the spherical depressions are configured to receive expansion of the plurality of silicon particles when the silicon particles are in a lithiated state;
[0042] a cathode electrode; and
[0043] Electrolytes.
[0044] Option 7. The battery cell according to Option 6, wherein each of the plurality of spherical depressions includes a portion of the plurality of silicon particles; and
[0045] Wherein, when the plurality of silicon particles are in an unlithiated state, each of the plurality of spherical depressions comprises an internal volume that is at least three times the volume of the silicon particle in the unlithiated state.
[0046] Option 8. A battery cell according to Option 6, wherein each of the plurality of silicon particles is permanently bonded to the inner wall of the plurality of spherical depressions, so that the plurality of silicon particles remain in conductive contact with the surface material through a lithiated state and a non-lithiated state.
[0047] Option 9. A battery cell according to Option 6, wherein the porous carbonaceous anode electrode coating is doped with nitrogen, phosphorus, silver, tin or lithium alloying atoms to anchor the silicon to the surface material.
[0048] Solution 10. A method for manufacturing an anode electrode for a lithium-ion battery cell, the anode electrode comprising silicon and a porous carbonaceous anode electrode coating, the method comprising:
[0049] attaching a plurality of silicon particles to each of a plurality of low temperature burnout particles configured to vaporize as a result of a burnout process;
[0050] producing a mixture comprising the plurality of low temperature burnout particles configured to vaporize as a result of a burnout process, a polymer material configured to produce conductive graphite as a result of the burnout process, and carbon particles, each of the low temperature burnout particles comprising the plurality of silicon particles;
[0051] applying the mixture as a plurality of active material particles to an electrode substrate;
[0052] A burnout process is performed on the plurality of active material particles, wherein the burnout process:
[0053] converting the polymer material into the graphite to form a conductive surface material of the plurality of active material particles;
[0054] vaporizing a plurality of low temperature burnout particles configured for vaporization as a result of a burnout process, thereby leaving a plurality of spherical depressions in the surface material, one of the plurality of spherical depressions for each of the plurality of low temperature burnout particles being configured for vaporization as a result of the burnout process; and
[0055] causing the plurality of silicon particles to adhere to inner walls of the plurality of spherical depressions; and
[0056] The spherical depressions are configured to receive expansion of the plurality of silicon particles when the silicon particles are in a lithiated state.
[0057] Embodiment 11. The method of embodiment 10, wherein attaching the plurality of silicon particles to each of the plurality of low-temperature burnout particles configured to evaporate as a result of the burnout process comprises attaching the plurality of silicon particles to a plurality of polystyrene foam balls.
[0058] Option 12. The method according to Option 10 also includes: selecting a plurality of low-temperature burnout particles configured to evaporate due to a burnout process in a size range configured such that the volume of the low-temperature burnout particles configured to evaporate due to a burnout process is at least three times the volume of silicon particles in an unlithiated state.
[0059] Option 13. A method according to Option 10, wherein attaching the plurality of silicon particles to each of the plurality of low-temperature burnout particles configured to evaporate due to the burnout process includes: rolling the plurality of low-temperature burnout particles configured to evaporate due to the burnout process in silicon dust.
[0060] Option 14. The method according to Option 10, wherein applying the mixture to the electrode substrate comprises: applying the mixture as a slurry.
[0061] Option 15. The method according to Option 10, wherein applying the mixture to the electrode substrate comprises: applying the mixture by an electrodeposition process.
[0062] Option 16. The method according to Option 10, wherein applying the mixture to the electrode substrate comprises: utilizing a vacuum drum device on the electrode substrate to achieve a desired dispersion of the active material particles on the electrode substrate.
[0063] Option 17. The method according to Option 10 also includes: doping the mixture with nitrogen, phosphorus, silver, tin, lithium alloying materials or conductive atoms to anchor the silicon particles to the inner wall.
[0064] Option 18. The method according to Option 10 also includes: adding a binder, carbon black or carbon nanotubes to the mixture.
[0065] The above features and advantages and other features and advantages of the present disclosure are readily apparent from the following detailed description of the best modes for carrying out the disclosure when taken in connection with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 is a schematic diagram of an electrical energy storage unit for powering a load according to the present disclosure, the energy storage unit being shown as a lithium ion (Li-ion) battery with respect to three-dimensional (XYZ) space, with corresponding positive and negative unit electrodes;
[0067] Figure 2A According to the present disclosure Figure 1 Schematic close-up cross-sectional side view of a representative electrode shown in , the representative electrode having a current collector fixed to an electrode substrate, wherein the current collector has a three-dimensional (3-D) porous structure;
[0068] Figure 2B According to the present disclosure Figure 2A Schematic close-up cross-sectional side view of the layers of various coatings of the electrode shown in , the base prior to the current collector, which is shown to have variable porosity;
[0069] Figure 3A According to the present disclosure Figure 1 Schematic close-up cross-sectional side view of an alternative representative electrode shown in , the electrode having a current collector secured to an electrode substrate, wherein the current collector has a three-dimensional (3-D) porous structure;
[0070] Figure 3B According to the present disclosure Figure 3A Schematic close-up cross-sectional side view of the layers of various coatings of the electrode shown in , the base prior to the current collector, which is shown to have a constant porosity;
[0071] Figure 4A is a schematic close-up top view of a three-dimensional porous structure coated with an interfacial layer, and a conductive additive and / or a polymer binder, and active material particles embedded within the porous structure according to the present disclosure;
[0072] Figure 4B is a schematic close-up top view of a three-dimensional porous structure coated with an interfacial layer and a conductive additive and / or a polymer binder according to the present disclosure, and the three-dimensional porous structure is free of active material particles embedded within the porous structure;
[0073] Figure 5 Schematically shows the Figure 1 , Figure 3A and Figure 4A An exemplary surface of an active material particle of;
[0074] Figure 6 The cross section schematically shows Figure 5 According to the present disclosure, the surface material of the active material particle is shown;
[0075] Figure 7 Schematically shows the Figure 6 of holes, where Figure 6 The silicon particles have been transformed into lithiated silicon particles;
[0076] Figure 8 schematically illustrates an active material particle during a manufacturing process prior to performing a burnout event on the active material particle in accordance with the present disclosure;
[0077] Fig. 9 is a flow chart illustrating a first exemplary method for making the disclosed active material particles and corresponding anode coatings according to the present disclosure;
[0078] Fig.10 is a flow chart illustrating a second exemplary method for making the disclosed active material particles and corresponding anode electrode coatings according to the present disclosure; and
[0079] Fig.11 An alternative exemplary process for fabricating an anode electrode according to the present disclosure is shown. DETAILED DESCRIPTION
[0080] Energy density describes how much energy a battery contains in proportion to the weight of the battery. A higher energy density reflects a higher capacity of the battery to deliver energy. A battery cell includes an anode and a cathode. The cathode may be described as a cathode electrode. The anode or anode electrode includes a current collector, which is typically a conductive film such as copper, and an anode electrode coating. The current collector of the anode may be a three-dimensional current collector, such as a three-dimensional mesh, having a complex surface that can be used to increase the surface area of the current collector, as described herein. The cathode includes a current collector and a cathode electrode coating. The anode electrode coating may include an anode active material coating, a binder, and a conductive material. The cathode electrode coating may include a cathode active material coating, a binder, and a conductive material. The chemical properties of the anode active material and the cathode active material are utilized to generate and control the electrochemical reactions that occur in the battery cell.
[0081] Specific materials can be used to increase the energy density of the battery cell. Silicon can be used in the anode active material to increase the energy density of the battery cell. During the battery cell discharge cycle, lithium ions move from the active material coating of the anode electrode to the active material coating of the cathode electrode. During the battery cell charge cycle, lithium ions move from the cathode electrode coating to the anode electrode coating. In the presence of lithium, the silicon particles change significantly in size. Although there is no lithium, the silicon particles are relatively small. In the presence of lithium, the silicon particles expand or expand greatly. In the presence of lithium, the silicon of the anode electrode can increase in size by 300%. The anode electrode will increase in volume in proportion to the amount of silicon in the anode electrode coating mixture. This overall outward expansion of the anode electrode coating quickly leads to rupture and failure of the anode electrode coating.
[0082] An anode electrode coating and a method for preparing the same are provided, wherein the anode electrode coating comprises active material particles, the active material particles being porous and comprising silicon particles fixed to the inner surface of the pores, such that when exposed to lithium, the silicon particles expand into the voids of the pores. This expansion of the silicon particles into the voids of the pores of the anode electrode coating enables the silicon particles to expand without significantly changing the overall size of the anode electrode coating. In one embodiment, the disclosed electrode may be configured to expand due to silicon lithiation, the expansion being in the range of 3% increase in electrode volume to 5% increase in electrode volume compared to an electrode having unlithiated silicon. In another embodiment, the disclosed electrode may be configured to expand due to silicon lithiation, the electrode volume increasing by up to 10% compared to an electrode having unlithiated silicon. In this way, the silicon load or amount of silicon present on the anode electrode coating may be increased, thereby increasing the energy density of the anode without causing damage to the anode electrode coating.
[0083] According to an exemplary method of manufacturing the disclosed active material particles, polymer beads with low volatilization temperatures, such as polystyrene foam, can be manufactured. In other exemplary embodiments, the polymer spheres can be constructed of cellulose acetate, polyethylene, polybutylene or polypropylene. The polymer spheres can be selected or configured to evaporate at the temperature used in the selected burnout process. The size of the polymer spheres can be selected or ensured to be approximately or at least three times the size of the unlithiated silicon to be added thereto. The exterior of the polymer spheres can be further coated with silicon nanoparticles of appropriate size for lithium-ion batteries. The total amount of silicon attached to the polymer spheres (wherein the silicon is in an unlithiated state) can be further selected or ensured to be approximately one-third of the volume of the polymer spheres. In an optional step, a polymer sphere with silicon adhered to the polymer spheres, i.e., a composite sphere, can be coated with an adhesive, a binder, carbon or a polymer material. Compared to the polymerized spheres, the outer polymer material or polymer material surrounding the polymer spheres before the burnout process can be a second polymer type and can be selected or configured to carbonize or transform into conductive graphite at the temperature used in the selected burnout process. The polymerized spheres are configured to vaporize during the burnout process, and the polymerized material is configured to transform into conductive graphite during the burnout process. The outer polymer material may be further mixed with an anode material including carbon particles, one or more binders, carbon black, carbon nanotube additives, and / or other ingredients used in lithium ion battery anodes in the art.
[0084] In an optional step, the composite sphere may be coated with an additive or carbon material and may be mixed with an additive to dope the carbonized polymer material with nitrogen, phosphorus, silver, tin, lithium alloying material, conductive atoms, or another suitable material for the purpose of bonding (bonding) or alloying to silicon to hold it in place in the walls of the void space. The bond may be between additional lone pairs of electrons in the dopant (such as in nitrogen or phosphorus), or by forming ionic or covalent bonds through the alloying metal.
[0085] In addition, the anode can be baked and the polymer balls and polymer materials can be burned out / carbonized. The wet anode can be dried at low temperatures. The polymer balls can be further burned out at medium temperatures to produce void spaces for silicon nanoparticles embedded in the polymer walls of the void spaces. In alternative operations, the polymer balls used to produce the void spaces can be placed in a "vacuum oven", the pressure in the oven can be reduced, and a relatively low temperature can be used to evaporate the polymer balls. The polymer material can be additionally carbonized into graphite carbon suitable for lithium-ion battery anodes. Due to the burnout process, in which the polymer balls are evaporated and the outer polymer material is carbonized into graphite, the silicon nanoparticles are embedded in the conductive graphite walls of the void spaces. Silicon will maintain high conductivity in all charge states. The void space is designed to fully accommodate the expansion of silicon when it is charged, lithiated, and undergoes a volume expansion of about 300% compared to silicon in an unlithiated state.
[0086] Figure 1 An energy storage unit for powering a load is schematically shown in a side view, and the energy storage unit is shown as a lithium ion (Li-ion) battery relative to a three-dimensional (XYZ) space, with corresponding positive and negative cell electrodes. An energy storage unit 10 for powering a load 12 is shown. As shown, the energy storage unit 10 has an anode (negative electrode) 14, a cathode (positive electrode) 16, and one of a solid, liquid, gel or non-aqueous polymer (e.g., polymer-based) electrolyte 18 that surrounds the anode, cathode and saturates the separator 20. The storage unit 10 is specifically shown as a lithium ion (Li-ion) battery. The anode 14 may include a three-dimensional mesh collector and may be composed of lithium, graphite, silicon, silicon oxide, and various other suitable materials. Although the cathode 16 is typically composed of a lithium ion battery cathode material, materials such as lithium manganese oxide, lithium iron phosphate, lithium nickel / manganese / cobalt oxide, or a variety of other suitable materials may also be used.
[0087] Lithium-ion batteries are rechargeable electrochemical cells that are distinguished by their high specific energy and low self-discharge. Lithium-ion batteries can be used to power a variety of items such as toys, consumer electronics, and motor vehicles. Although the electrical energy storage unit 10 is specifically shown as a lithium-ion battery, it is broadly contemplated that other battery chemistries and corresponding structures are also contemplated. The vehicle may include, but is not limited to, a commercial vehicle, an industrial vehicle, a passenger vehicle, an aircraft, a ship, a train, and the like. It is also contemplated that the vehicle may be a mobile platform such as an airplane, an all-terrain vehicle (ATV), a boat, a personal mobility device, a robot, and the like to achieve the purposes of the present disclosure.
[0088] In a lithium-ion battery, lithium ions move from the anode 14 through the electrolyte 18 to the cathode 16 during discharge, and back during charging. Lithium-ion batteries use lithium metal oxides (e.g., Li-NMC, Li-NMCA, LMO, NMO, LFP, etc.) as the material at the positive electrode, and typically use graphite as the material at the negative electrode. Typically, the reactants in the electrochemical reaction in the lithium-ion cell 10 are the materials of the anode and cathode, both of which are compounds that can accommodate lithium atoms. During discharge, the oxidation half-reaction at the anode 14 produces positively charged lithium ions and negatively charged electrons. The lithium ions move through the electrolyte 18 and the electrons move through the external circuit (including a connection to an electrical load 12 or a charging device), and then they recombine at the cathode (together with the cathode material) in a reduction half-reaction.
[0089] The electrolyte 18 and the external circuit provide a conductive medium for lithium ions and electrons, respectively, but do not participate in the electrochemical reaction. In general, during discharge of an electrochemical cell, electrons flow between the electrodes from the anode 14 to the cathode 16 through the external circuit. The reaction during discharge reduces the chemical potential of the cell, so the discharge transfers energy from the cell to wherever the current dissipates its energy, primarily in the external circuit. During charging, the reaction and transfer occur in the opposite direction: electrons move from the positive electrode to the negative electrode through the external circuit. In order to charge the cell, the external circuit must provide electrical energy. This energy is then stored (with some losses) in the cell as chemical energy.
[0090] In a lithium-ion cell, both the anode 14 and the cathode 16 allow lithium ions to move into and out of their structures by a process known as insertion (intercalation) or extraction (deintercalation), respectively. Typically, the anode 14 employs a current collector that may be made of copper and includes an active layer configured to intercalate lithium ions. Typically, the amount of lithium held by the active layer is directly related to the performance of the lithium-ion battery. In addition, the ability of the active layer to intercalate lithium is limited by its physical or material molecular structure. Therefore, an increase in the amount of lithium held by an electrode (e.g., anode 14) will benefit the performance of the lithium-ion battery cell 10, such as cycle capacity.
[0091] The specific configuration of the electrodes for the lithium-ion battery cell 10, such as the anode 14 (or cathode 16), is configured to maximize the amount of lithium retained by it during charging and discharging. In the case of the anode in particular, lithium combines with silicon during charging, which results in significant expansion of the silicon. The configuration of the electrode, which will be described in detail below, is specifically configured to accommodate silicon expansion during charging and also allow lithium ions to be transported into and out of the electrode structure after expansion. The electrode includes an electrode substrate 22, which may be composed of a portion of a metal foil (commonly referred to as a collector foil) defined by a thickness T, a width W, and a length L. The electrode may also include a current collector 24 fixed to (e.g., adhered to or formed on) the electrode substrate 22. In one embodiment, the current collector 24 may be a flat sheet of flexible foil, which may have a slurry applied to the foil in a roll-to-roll operation. The foil may include a structure added on top of the foil to produce a three-dimensional structure as described herein. The current collector 24 may be fixed to the electrode substrate 22 by a process of electroplating, electrochemical deposition, physical deposition, or welding. Specifically, the material of the current collector 24 may be electrochemically deposited onto the surface of the electrode substrate 22 to produce the electrode of the battery cell 10. Each of the electrode substrate 22 and the current collector 24 may be composed of or consist of copper.
[0092] like Figure 2A-Figure 4B As shown, the resulting current collector 24 applied to the electrode substrate 22 has a three-dimensional (3D) porous structure 26 that defines a plurality of interstitial void spaces 28 (eg, created by contacting, crossing and / or interweaving fibers) (eg, as shown in FIG. 3- Figure 4B As shown). The current collector 24 may be, for example, Figure 1 The anode 14 structure is provided as shown. The void space 28 is configured to accommodate active material particles 30 therein, such as active material particles 30 of a lithium alloy material. In addition, before the initial charging of the battery cell 10, the void space 28 can be pre-filled and / or covered with a polymer, gel or glass / ceramic electrolyte 18. Specifically, although the void spaces 28 are generally left open and unfilled, they can be pre-filled with a gel or soft polymer electrolyte 18. In addition, the top surface of the current collector 24 can be covered with a polymer or solid glass / ceramic electrolyte 18 to seal the surface of the current collector relative to the separator 20.
[0093] The term "three-dimensional porous" is used herein to refer to a collector structure that includes pores of varying or non-uniform size in three-dimensional space (e.g., in a direction orthogonal to the mounting surface 22A of the electrode substrate 22). The three-dimensional porous structure 26 may also be referred to as "controlled porosity," which herein refers to a collector body having a specifically defined variable porosity distribution and non-uniformly sized included pores. The specific distribution of variable porosity in the three-dimensional porous structure 26 is intended to promote effective internal expansion volume rather than external expansion volume of the embedded active material particles 30 attached to the collector 24 during charging of the battery cell 10.
[0094] like Figure 2A and Figure 2B As shown in , the three-dimensional porous structure 26 may include nodes 32 formed by pore walls 34. The pore walls 34 define void spaces 28. The three-dimensional porous structure 26 may also have a porosity of variable size, that is, the void spaces 28 may have variable sizes. The three-dimensional porous structure 26 may also be characterized by a porosity gradient G defined by the pore walls 34, the thickness 34A of the pore walls gradually increasing as it approaches the electrode substrate 22. An electrodeposited adhesion layer or a vapor deposition adhesion layer may be added to fibers that are not initially connected to each other, thereby producing cross nodes 32. The nodes 32 may also increase in thickness as they are closer to the mounting surface 22A of the electrode substrate 22 to carry higher currents. Therefore, the gradient G may be purposefully configured to support a relatively high energy density load (relative to a density load closer to the outer surface of the collector) on the current collector 24 near the electrode substrate 22 during charging of the battery cell 10.
[0095] The pore walls 34 may include a coating 36 applied thereto. The coating 36 may be applied by a polymer coating or a particle coating, and in certain embodiments is configured to produce a gradient G. The polymer coating and the particle coating may be applied by a variety of options, such as dip coating and drum drying, spray coating, slurry coating with a slot die, roller coating in a wet / dry particle bed, fluidized air particle bed, thermal (vapor) deposition, vacuum drum coating, and drying (filtration). Specifically, the coating 36 may include one or more layers of an adhesive or binder configured to secure the active material particles 30 to the pore walls 34. As Figure 2A As shown in FIG, in an embodiment where the porosity of the base current collector 24 is variable (eg Figure 2B ), the coating 36 may have a constant thickness 36A. Alternatively, as shown in Figure 3A As shown in FIG. , in an embodiment where the porosity of the base current collector 24 is constant (eg Figure 3B ), the coating 36 may have a varying thickness 36B. Thus, as shown Figure 2A and Figure 3AAs can be seen in FIG. 1 , in either embodiment, the resulting three-dimensional porous structure 26 will have the size of the void spaces 28 gradually increasing with increasing distance from the electrode substrate 22, thereby defining a gradient G.
[0096] The active material particles 30 will be applied to the three-dimensional porous structure 26 as a coating, so that the active material particles become arranged and dispersed within the void spaces 28 of the three-dimensional porous structure. As a result, the charging of the battery cell 10 using the electrode reversibly deposits transient (e.g., lithium) ions onto the active material particles 30, and expands (or swells) the active material particles into the void spaces 28 of the three-dimensional porous structure 26, thereby generating an interstitial active material collector structure. On the other hand, the discharge of the battery cell 10 using the electrode extracts transient ions from the active material particles 30, causing the active material to shrink from the void spaces 28 of the three-dimensional porous structure 26. Therefore, the battery cell 10 can undergo repeated intercalation and deintercalation cycles of lithium ions in the process of accepting charge from an external energy source (e.g., a power grid) and then supplying charge to power the load 12.
[0097] Figure 4A and 4B Each of the three-dimensional porous structure 26 depicts a top view of the three-dimensional porous structure 26 in which active material particles 30 are embedded and not embedded, respectively. Figure 4A and Figure 4B As shown in , the current collector 24 may be coated with an interface layer 38 configured to attract and / or adhere to the active material particles 30. In addition, the current collector 24 may be coated with a conductive additive 40A and / or an elastic polymer binder 40B. In an embodiment where the current collector 24 is coated with a polymer binder 40B, the binder may then be cured, polymerized, carbonized and / or graphitized, for example, in a vacuum, an oven and / or with infrared or ultraviolet light. The current collector 24 may be pre-coated with active material particles 30. In such an embodiment, the pre-coated active material particles 30 may be provided in the form of a wet carbon-silicon electrode slurry, solid particles, a polymer coating mixed with silicon particles, or solid lithium. Pre-coating can be used to "pre-lithiate" the lithium-ion battery anode 14, that is, effectively pre-charge, and mitigate the irrecoverable loss of lithium during the initial cycle of the battery cell 10 and increase the total cycle capacity of the battery cell.
[0098] The electrode using the three-dimensional porous structure 26 can be subjected to final curing to keep the active material particles 30 in place, and also evaporate the low temperature material, such as evaporating from the carbon-silicon slurry. The manufacture of the current collector 24 may also include removing excess active material particles 30 from the current collector 24. This removal of excess active material particles 30 can be achieved by running the current collector 24 externally on a vacuum drum, by blowing the three-dimensional porous structure 26 with a pressurized gas stream, or by stirring the current collector 24 on a vibrating table. The completed current collector 24 is intended to provide a three-dimensional porous structure 26, which can accommodate an increased volume of embedded active materials compared to a current collector with a pore structure of uniform size or a non-porous structure (having a similar external surface area).
[0099] Figure 5 Schematically shows Figure 1 , Figure 3A and Figure 4A 30. For illustration purposes, the composition and structure of the surface of the active material particle 30 is shown as a flat surface. The surface of the active particle 30 may be curved, spherical, or irregular, and Figure 5 The illustrated surface is for non-limiting illustration only. The surface material 140 includes a polymerized binder material that carbonizes or burns out to form a conductive carbon. Hard carbon particles 110 are illustrated as being dispersed within the surface material 140. The hard carbon particles 110 may alternatively be described as active anode carbon, such as mesocarbon particles. The pores 120 are illustrated as including depressions formed in the surface material 140 and creating pores of active material particles 30. A plurality of silicon particles 130 are attached, fixed or bonded to the walls of the pores 120. As described herein, the silicon particles 130 react with lithium ions and, when present, increase the energy density of a battery cell in which an anode electrode coating is disposed.
[0100] Electrode coatings used in the art may be porous so that electrolytes or other materials can interact with the coating. The disclosed electrode coatings may similarly include pores configured to enable the electrode coating to interact with other materials. The disclosed electrodes and methods additionally and / or alternatively include pores that include the disclosed silicon material embedded within the pores 120 to enable lithiation of the silicon particles 130 within the pores 120, the lithiation combined with the three-dimensional current collector enables control of the overall expansion of the corresponding electrode and increases the silicon content.
[0101] The surface material 140 and the walls of the pores 120 include a conductive carbon material. In one embodiment, the surface material 140 may be described as graphite.
[0102] Figure 6 The cross section schematically shows Figure 51. The surface material 140 of the active material particle 30 is shown. The pore 120 can be described as a depression or curved shape in the surface material 140, which creates a void space 150 in the surface material 140. The void space 150 can be described as an area where the liquid electrolyte of the battery cell can enter and lithium ions can flow into. The silicon particle 130 is shown attached to or embedded in the wall 122 of the pore 120. Because the surface material 140 is carbonized and conductive, the silicon particle 130 is in solid or permanent contact with the wall 122, and therefore has a strong conductive contact with the surface material 140. Figure 6 The silicon particles 130 are shown in a non-lithiated state, and therefore have a relatively small size.
[0103] As part of the method of forming active material particles 30 as described herein, silicon particles 130 may be embedded within the walls 122 of the pores 120. In one embodiment, the active material particles 30 may include silicon particles 130 embedded in the outer layer of hollow carbon spheres or spherical depressions in the surface material 140, wherein the pores 120 form a hollow space or a portion of a hollow space within the carbon body of the active material particles 30. In one embodiment, the active material particles may be doped with nitrogen, phosphorus, silver, tin, or other similar additives to anchor the silicon particles to the surface material 140.
[0104] Figure 7 Schematically shows Figure 6 The hole 120, wherein Figure 6 The silicon particles 130 have been transformed into lithiated silicon particles 130'. The lithiated silicon particles 130' remain attached to the walls of the pores 120. The lithiated silicon particles 130' are relatively larger than Figure 6 Silicon particles 130. In one embodiment, Figure 7 The lithiated silicon particles 130' may be Figure 6 300% of the unlithiated silicon particles 130. The void space 150 provides a volume in which the lithiated silicon particles 130' can expand without changing the external shape of the active material particles 30. In this way, silicon can be used within the active material particles 30 to increase the energy density of the battery cell without incurring the negative impact of rapid expansion of the active material particles and causing cracking or failure of the anode electrode coating. In one embodiment, the active material particles 30 can be configured to have no external volume expansion. In another embodiment, the active material particles can be configured for a smaller or acceptable volume expansion (e.g., when the silicon particles 130 are converted from an unlithiated state to a lithiated state, the active material particles are allowed to grow in size by 5% by volume).
[0105] Figure 8 An active material particle 30 is schematically shown during the manufacturing process prior to performing a burnout event on the active material particle. In one embodiment, Figure 8 The active material particles 30 in the figure represent slurry particles, wherein the polymer material 140' is configured to produce conductive graphite as a result of a burnout process. The polymer material 140' can be in a liquid, paste, or colloidal state. Low-temperature burnout polymer particles 170 are shown within depressions in the polymer material 140', which are configured to produce conductive graphite as a result of a burnout process. The low-temperature burnout particles 170 are selected based on the material of the low-temperature burnout particles 170 that evaporates within the temperature range of a burnout event. The low-temperature burnout particles 170 can be described as low-temperature burnout particles that are configured to evaporate as a result of a burnout process. The low-temperature burnout particles 170 can be composed of polystyrene foam, for example, commercially available through DDP Specialty Electronic Materials US, Inc. Corporation of Wilmington, Delaware, USA. In other embodiments, similar low temperature polymer materials may be used. The low temperature burnout particles 170 may be rolled or placed in a silicon dust or silicon particle bath prior to being placed in the polymer material 140'. The silicon particles 130 are attached or adhered to the low temperature burnout particles 170, and the low temperature burnout particles 170 with the silicon particles 130 adhered thereto may be introduced into the polymer material 140'. Figure 5 The carbon particles 110 may be additionally introduced into the polymer material 140'. At the completion of the burnout event, the low temperature burnout particles 170 are vaporized, the polymer material 140' is carbonized, and the silicon particles 130 remain fixed in the Figure 6 The holes 120 are formed in the holes 120 which are left when the low temperature burnt-out particles 170 are evaporated.
[0106] The disclosed active material particles 30 may have silicon particles 130 embedded in the walls of hollow spheres or spherical depressions to always maintain electrical contact with the electrode. Smaller silicon particles may be used. A method for manufacturing the disclosed active material particles 30, an anode electrode coating using active material particles 30, or a battery cell using an anode electrode coating using active material particles 30 is provided. The method uses binder burnout to produce hollow spheres or spherical depressions of void spaces. The method is very suitable for using carbonized polymers as electrode carbon or surface materials 140. The size of the polymer burnout ball (i.e., low temperature burnout particle 170) may be approximately or at least three times the size of the unlithiated silicon attached to the polymer burnout ball, so as to produce three times the void space for expanding the silicon particles 130 during full lithiation. The silicon particles 130 may be described as nanoparticles. The nanoparticles are embedded in the conductive graphite walls of the void space. The silicon particles 130 will maintain high conductivity with the connected surface material 140 at each state of charge. The void spaces may be sized to fully accommodate the expansion of the silicon particles 130 as they charge, lithiate, and undergo a volume expansion of approximately 300% compared to the silicon particles 130 in their un-lithiated state.
[0107] like Figure 4A As shown in FIG. 3 , active material particles 30 may be applied to the three-dimensional porous structure 26 and / or the interfacial layer 38. The active material particles 30 may be prepared and applied according to a variety of alternative method steps. Fig. 9 and Fig.10 Provided are methods for preparing and applying active material particles 30 and producing Figure 1 The disclosed steps are exemplary, many alternative or additional method steps may be envisioned, and the present disclosure is not intended to be limited to the examples provided.
[0108] The current collector can have complex shapes, e.g. Figure 2A-Figure 3B The disclosed method can be used with other current collector configurations. Fig.11An alternative exemplary process 400 for producing an electrode according to the present disclosure is shown. A current collector 420 comprising a metal foil is shown. A dispenser mechanism 410 is shown connected to a premixed slurry. The dispenser mechanism 410 is shown dispensing an electrode coating 430 onto the current collector 420. The electrode coating 430 is a slurry and includes a polymer material 440 configured to produce conductive graphite as a result of a burnout process, a plurality of graphite particles 450, and a plurality of low-temperature burnout particles 460 configured to evaporate as a result of the burnout process, each low-temperature burnout particle 460 being coated with a plurality of silicon nanoparticles 470. Once the burnout process is performed on the electrode coating 430, the polymer material 440 is transformed into a conductive graphite material, and the low-temperature burnout particles 460 evaporate, leaving behind the silicon nanoparticles 470 attached to the pore walls in the surface of the electrode coating 430. Many additional and / or alternative process steps are contemplated, and the present disclosure is not intended to be limited to the examples provided herein.
[0109] Fig. 9 is a flow chart illustrating a first exemplary method 200 for making the disclosed active material particles and corresponding anode electrode coatings. The method 200 is based on various Figure 1-Figure 8 , while method 200 may be operated with similar but different components. Method 200 begins at step 202. At step 204, a plurality of low temperature burnout particles configured for vaporization due to the burnout process 170, such as, for example, styrofoam balls, are preselected for a particular size based on the silicon particles 130 and the total desired silicon content to be included in the resulting anode electrode coating. These low temperature burnout particles configured for vaporization due to the burnout process 170 are dipped or rolled in a silicon dust or silicon particle bath such that the low temperature burnout particles configured for vaporization due to the burnout process 170 include some silicon particles 130 attached or fixed to the exterior of the low temperature burnout particles configured for vaporization due to the burnout process 170. Step 204 may additionally include adding additives or dopants as described herein. At step 206, the composite balls, i.e., the low temperature burnout particles including attached silicon particles 130 configured for vaporization due to the burnout process 170, are added to a polymer material slurry, which may include carbon particles, a binder, and other additives. At step 208, an electrode substrate is prepared or selected. The electrode substrate may include Figure 4A The three-dimensional porous structure 26 and / or the interface layer 38. At step 210, the slurry mixture of step 206 is applied to the electrode substrate. Figure 3BAs described above, a vacuum drum device or other similar device may be used to manipulate the position of the active material particles 30 and achieve a desired dispersion of the active material particles 30. At step 212, a baking process is applied to burn out the low temperature burnout particles configured to evaporate due to the burnout process 170, thereby leaving a porous structure on the surface of the active material particles 30, wherein the silicon particles 130 are attached to the inner walls of the pores 120. In addition, the burnout process converts the polymer material of the slurry into a hardened and conductive surface material 140. At step 214, the coated electrode substrate is assembled to a battery cell and used in the operation of the battery cell. At step 216, the method 200 ends.
[0110] Fig.10 is a flow chart showing a second exemplary method 300 for making the disclosed active material particles and corresponding anode electrode coatings. The method 300 is based on various Figure 1-Figure 8 , while method 300 may be operated with similar but different components. Method 300 begins at step 302. At step 304, a plurality of low temperature burnout particles configured to be vaporized due to the burnout process 170, such as foam polystyrene balls, are preselected for a particular size based on the silicon particles 130 and the total desired silicon content to be included in the resulting anode electrode coating. These low temperature burnout particles configured for vaporization due to the burnout process 170 are immersed or rolled in a silicon dust or silicon particle bath so that the low temperature burnout particles configured for vaporization due to the burnout process 170 include some silicon particles 130 attached or fixed to the exterior of the low temperature burnout particles configured for vaporization due to the burnout process 170. Step 304 may additionally include adding additives or dopants as described herein. At step 306, these composite balls, i.e., the low temperature burnout particles configured for vaporization due to the burnout process 170 including attached silicon particles 130, are added to a polymer material mixture, which may include carbon particles, a binder, and other additives. At step 308, an electrode substrate is prepared or selected. The electrode substrate may include a sheet of material in a roll-to-roll operation. The electrode substrate may receive or include a three-dimensional porous structure 26, which may be achieved by a copper electrodeposition process. The electrode substrate may additionally or alternatively receive Figure 4A At step 310, the polymer material mixture of step 306 is applied to the electrode substrate by an electrodeposition process, wherein an electric field is used to cause the charged particles to adhere to the electrode substrate. Figure 3BAs described above, a vacuum drum device or other similar device may be used to manipulate the position of the active material particles 30 and achieve a desired dispersion of the active material particles 30. At step 312, a baking process is applied to burn out the low temperature burnout particles configured to evaporate due to the burnout process 170, thereby leaving a porous structure on the surface of the active material particles 30, wherein the silicon particles 130 are attached to the inner walls of the pores 120. In addition, the burnout process converts the polymer material of the slurry into a hardened conductive surface material 140. At step 314, the coated electrode substrate is assembled to a battery cell and used in the operation of the battery cell. At step 316, the method 300 ends.
[0111] While the best modes for carrying out the disclosure have been described in detail, those familiar with the art to which this disclosure relates will recognize various alternative designs and embodiments for practicing the disclosure within the scope of the appended claims.
Claims
1. An anode electrode for a lithium-ion battery cell, the anode electrode comprising silicon and a porous carbon anode electrode coating, the anode electrode comprising: an electrode substrate including a current collector; as well as A porous carbonaceous anode electrode coating comprising: A surface material comprising graphite, wherein the surface material comprises a plurality of spherical depressions; Carbon particles; and A plurality of silicon particles are attached to inner walls of the plurality of spherical depressions, wherein the spherical depressions are configured to receive expansion of the plurality of silicon particles when the silicon particles are in a lithiated state.
2. The anode electrode according to claim 1, wherein Each of the plurality of spherical depressions includes a portion of the plurality of silicon particles; as well as Wherein, when the plurality of silicon particles are in an unlithiated state, each of the plurality of spherical depressions includes an internal volume that is at least three times the volume of the silicon particle in the unlithiated state.
3. The anode electrode according to claim 1, wherein Each of the plurality of silicon particles is permanently bonded to an inner wall of the plurality of spherical depressions such that the plurality of silicon particles remain in conductive contact with the surface material through the lithiated state and the un-lithiated state.
4. The anode electrode according to claim 1, wherein The porous carbonaceous anode electrode coating is doped with nitrogen, phosphorus, silver, tin, lithium alloying materials or conductive atoms to anchor the silicon to the surface material.
5. The anode electrode according to claim 1, wherein When the plurality of silicon particles are in the lithiated state, the anode electrode expands in volume in a range of 0% to 5% compared to a volume of the anode electrode when the plurality of silicon particles are in the un-lithiated state.
6. A battery cell comprising an anode electrode for a lithium ion battery cell, the anode electrode comprising silicon and a porous carbonaceous anode electrode coating, the battery cell comprising: The anode electrode comprises: an electrode substrate including a current collector; and The porous carbon anode electrode coating comprises: A surface material comprising graphite, wherein the surface material comprises a plurality of spherical depressions; Carbon particles; and a plurality of silicon particles attached to inner walls of the plurality of spherical depressions, wherein the spherical depressions are configured to receive expansion of the plurality of silicon particles when the silicon particles are in a lithiated state; a cathode electrode; and Electrolytes.
7. The battery cell according to claim 6, wherein: Each of the plurality of spherical depressions includes a portion of the plurality of silicon particles; as well as Wherein, when the plurality of silicon particles are in an unlithiated state, each of the plurality of spherical depressions comprises an internal volume that is at least three times the volume of the silicon particle in the unlithiated state.
8. The battery cell according to claim 6, wherein: Each of the plurality of silicon particles is permanently bonded to an inner wall of the plurality of spherical depressions such that the plurality of silicon particles remain in conductive contact with the surface material through a lithiated state and an unlithiated state.
9. The battery cell according to claim 6, wherein: The porous carbonaceous anode electrode coating is doped with nitrogen, phosphorus, silver, tin or lithium alloying atoms to anchor the silicon to the surface material.
10. A method of making an anode electrode for a lithium-ion battery cell, the anode electrode comprising silicon and a porous carbonaceous anode electrode coating, the method comprising: attaching a plurality of silicon particles to each of a plurality of low temperature burnout particles configured to vaporize as a result of a burnout process; producing a mixture comprising the plurality of low temperature burnout particles configured to vaporize as a result of a burnout process, a polymer material configured to produce conductive graphite as a result of the burnout process, and carbon particles, each of the low temperature burnout particles comprising the plurality of silicon particles; applying the mixture as a plurality of active material particles to an electrode substrate; A burnout process is performed on the plurality of active material particles, wherein the burnout process: converting the polymer material into the graphite to form a conductive surface material of the plurality of active material particles; vaporizing a plurality of low temperature burnout particles configured for vaporization as a result of a burnout process, thereby leaving a plurality of spherical depressions in the surface material, one of the plurality of spherical depressions for each of the plurality of low temperature burnout particles being configured for vaporization as a result of the burnout process; and causing the plurality of silicon particles to adhere to inner walls of the plurality of spherical depressions; and The spherical depressions are configured to receive expansion of the plurality of silicon particles when the silicon particles are in a lithiated state.
